Selective cleaving the NP bond of difluoromethylene phosphabetaines for effective synthesis of β-ketoamides. Issue 29 (18th July 2019) - Liu, Yingle; Yang, Tao; Dong, Yuting; Cai, Junjie; Luo, Gen; Tong, Xia; Jiang, Yan; Yang, Yi; Xu, Xiu-Hua
Graphical abstract: Highlights: [Tris(dimethylamino)phosphonio]difluoroacetate ADFA is a novel aminating reagent. Selective cleaving NP bond of ADFA. An transition-metal and base-free protocol for the synthesis of β-ketoamides. Simple operation and wide substrate scope. Abstract: An unprecedent transition-metal-free protocol for the synthesis of β-ketoamides from β-ketoesters is described. This method involves selective cleaving NP bond of an unusual aminating reagent, [tris(dimethylamino)phosphonio]difluoroacetate (ADFA), which is well known as the difluoromethylene ylide precursor. The process is notable for its operational simplicity and good functional group tolerance.